(3aJGhi GdSHcis - (3Ydj Hf YHO GdcGaj Hf Ydj Hf JeGe GdSHcj GdCfUGQj GdNRQLj, CHh GdMSf, Jbqj GdOjf,J (B756 (3g` s ((3eMeO Hf GHQGgje s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf GdeSFdI GdChdi bGd GdTjN fLe GdOjf ai GdcaGjI C, HjY GdLRA hGdTdLe ai GdGQV bHd bdYg s
(3BNQgG (B:s
(3hGTJed Ydi UhQ gPg GdUhQI ajgG gPG GdNdGa hGLJfGHgG eMd GdhQY hGddg GYde s
(3HgG fXGe GdJYbjHIs
(3aQZ GdeDda ef JCdjagG SfI (B748 (3g`s
(3GdcJGH eWHhY hgPg fSNI fajSI cJHJ ai MjGI GdeDda hfbdJ ef NWg s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdESdGejs